Bevacizumab loaded CalliSpheres® bronchial arterial chemoembolization combined with immunotherapy and targeted therapy for advanced lung adenocarcinoma - Liu, Haitao; Li, Yahua; Li, Zongming; Han, Xinwei; Ren, Kewei (Frontiers in Pharmacology, 2023)
Background: As a new drug delivery and embolization system, drug-eluted bronchial artery chemoembolization (DEB-BACE) can not only embolize the tumor blood supply artery, but also load chemotherapy drugs and slowly release them into the local environment. Bevacizumab (BEV) combined with chemotherapy drugs has made great achievements in the first-line treatment of advanced non-squamous non-small cell lung cancer (NSCLC). The role of BEV loaded DEB-BACE combined with immunotherapy and targeted therapy in patients with lung adenocarcinoma (LUAD) is unclear. This study was designed to evaluate the efficacy and safety of bevacizumab loaded CalliSpheres® bronchial arterial chemoembolization combine with immunotherapy and targeted therapy in patients with lung adenocarcinoma. Methods: From Jan 1 2021 to Dec 2021, nine patients with LUAD received BEV-loaded CalliSpheres® BACE combine with immunotherapy and targeted therapy were included in this study. The primary endpoint was the disease control rate (DCR) and the objective response rate (ORR). The secondary endpoints were overall survival rate (OS) at 6 months and 12 months. The tumor response was evaluated according to the mRECIST standard. Safety was assessed by the occurrences of adverse events and severity adverse events. Results: All patients received CalliSpheres® BACE loaded with BEV (200mg) in combination with immunotherapy and targeted therapy. A total of nine patients received 20 times BACE procedures, four of them received a third session of BACE, three underwent a second session of DEB-BACE, and two underwent one cycle of DEB-BACE. Partial response, and stable disease were found in 7 (77.8%), and 2 (22.2%) patients, respectively, at 1month after the last multimodal treatment. The ORR at 1, 3, 6, 12months is 77.8%, 66.7%, 44.4%, 33.3%, while the DCR is 100%, 77.8%, 44.4% 33.3%. The OS rates at 6- and 12-month are 77.8% and 66.7%. There were no serious adverse events. Conclusions: BEV loaded CalliSpheres® transcatheter bronchial arterial chemoembolization combine with immunotherapy and targeted therapy is a promising and well tolerated treatment for patients with lung adenocarcinoma.